Pelatihan Ecoprint Berbasis Ekonomi Kreatif dalam Rangka Penguatan Nilai-Nilai Pancasila pada Masyarakat Desa Ngadirejo Kecamatan Salaman Kabupaten Magelang - Maryana, Maryana; Nisfia, Laila; Amrullah, Nafis Azmi (Universitas Negeri Semarang, 2023)
Training ecoprint can be a means for the community to collaborate on the use of natural materials by strengthening the values of Pancasila. Strengthening Pancasila values in this case is the use of natural materials as the main ingredient in making clothecoprint. Training ecoprint supports sustainable printing practices because it uses natural materials thereby reducing negative impacts on the environment, such as the use of chemical inks and synthetic materials. Ecoprint also has an interesting business potential. Ecoprint training the aim of community service activities in Ngadirejo Village is to empower community groups, especially PKK women to train business skills in producing products that have selling points to help improve the family and village economy. The method used in this research is qualitative research through literature studies. Data collection techniques used are observation and documentation. Presentation of the data is analyzed and presented in the form of descriptive qualitative narrative. Community service implementation activities are carried out through three stages, namely the preparatory, implementation, and final stages. Products produced from community service activities, namely clothecoprint which are ready to use and can be continued into sustainable products such as scarf, clothes, bags, or home decorations.